In silico high-throughput screening system for AKT1 activators with therapeutic applications in sepsis acute lung injury - Wang, Ziyi; Wang, Xuesong; Guo, Zhe; Liao, Haiyan; Chai, Yan; Wang, Ziwen; Wang, Zhong (Frontiers in Cellular and Infection Microbiology, 2022)
Purpose AKT1 is an important target in sepsis acute lung injury (SALI). The current study was aim to construct a high-throughput screening (HTS) system based on the ChemDiv database (https://www.chemdiv.com/complete-list/) and use the system to screen for AKT1 activation agents, which may provide clues for the research and development of new drugs to treat SALI. Methods Based on the existing X-ray structure of AKT1 and known AKT activators, a large-scale virtual HTS was performed on the ChemDiv database of small molecules by the cascade docking method and demonstrated both accuracy and screening efficiency. Molecular docking and molecular dynamics simulations were used to assess the stability and binding characteristics of the identified small-molecule compounds. The protective effect of the new highly selective compound on SALI were verified both in vitro and in vivo experiments. Results The small-molecule compound 7460-0250 was screened out as a specific activator of AKT1. Molecular validation experiments confirmed that compound 7460-0250 specifically promoted the phosphorylation of AKT1 and down-regulated the LPS-induced apoptosis of human umbilical vein endothelial cells (HUVECs) by activating the AKT-mTOR pathway. Up-regulated mTOR was detected to directly interact with Bax to reduce apoptosis. In vivo, compound 7460-0250 could improved survival rate and alleviated lung injury of sepsis mice induced by cecum ligation and puncture (CLP), parallel with the activation of the AKT-mTOR pathway. Conclusion Small-molecule compound 7460-0250 was successfully screened and confirmed as a highly selective AKT1 activator, which is a critical target in the development of new therapeutics for SALI.